A randomised controlled trial comparing the GlideScope® and the Macintosh laryngoscope for double‐lumen endobronchial intubation. (December 2013) - Russell, T.; Slinger, P.; Roscoe, A.; McRae, K.; Van Rensburg, A.
Summary Double‐lumen endobronchial tubes are the most common method of achieving lung isolation and one‐lung ventilation during thoracic anaesthesia and surgery. We compared the clinical performance of the Macintosh laryngoscope and the GlideScope® during endobronchial intubation with a double‐lumen tube. Seventy patients with no predictors for difficult laryngoscopy were allocated randomly to the Macintosh laryngoscope or GlideScope. The time taken for endobronchial intubation with the Macintosh laryngoscope was significantly shorter compared with that taken for the GlideScope, median (IQR [range]) 33 (22–52 [11–438]) s vs 70 (39–129 [21–242]) s, respectively, p = 0.0013. There was no statistical difference in the rate of success at the first attempt (91% vs 83%, respectively). On a numerical rating scale (scored from 0 to 10), the 30 anaesthetists who took part in the study rated endobronchial intubation overall as easier using the Macintosh compared with the GlideScope, 2 (1–3 [0–8]) vs 3 (2–6 [0–10]), respectively, p = 0.003. Postoperative voice changes were also less common in the Macintosh group (8 (22%) vs 17 (58%), p = 0.045). Anaesthetists found the GlideScope more difficult to use than the Macintosh laryngoscope and endobronchial intubation took longer; therefore, we cannot recommend its routine use with double‐lumen tubes in patients who are predicted to have a normal airway.